A Model for Social Capital and the Capital Cost - M. Safari Gerayli (Ph. D.); Y. Rezaei Pitenoei (Ph. D.) (حسابداری سلامت, 2020)
Introduction: Social capital, along with human and economic capital, has drawn considerable attention. It enhances the market participation and mitigates financing costs via promoting mutual trust Method: This research is applied in terms of purpose and is descriptive-correlation regarding the data collection. The aim of this study is to evaluate the relation between social capital and capital cost using the structural equations method. In this study, three methods of O’hanlon and Steele, Capital Asset Pricing Model and adjusted price-to-earnings ratio in an industry were employed to measure capital cost. Nahapiet and Ghoshal’s questionnaire was also adopted to compute social capital. Results: Having ensured the good-fitness of the appraisal and structural models, the research hypotheses were tested and the results reveal that social capital mitigates the capital cost. Conclusion: Policy makers should focus on social capital as the main component of management in organizations, and it is necessary to consider a variety of programs, such as encouraging the creation and strengthening of social institutions.